Reconnaissance Drought Index Based Evaluation of Meteorological Drought Characteristics in Bundelkhand. (2016) - Thomas, T.; Jaiswal, R.K.; Galkate, R.V.; Nayak, T.R.
Abstract: Among all the different types of extreme events drought is considered to be the most hazardous in terms economic losses and number of people being affected by its impacts, mainly due to the various complexities involved. Since it is rather difficult to predict and forecast droughts with a reasonable degree of certainty, the drought management aspects are also very complex and needs to be fine-tuned with the spatial and temporal variation of drought characteristics. It is therefore mandatory to evaluate the drought characteristics effectively for development of operative action oriented drought management plans. Generally there are many techniques available for the measurement of drought characteristics; however the drought indices can be effectively used to identify the characteristics of various types of droughts including the meteorological, hydrological and agricultural droughts. TheReconnaissance Drought Index (RDI) have been applied to evaluate the characteristics of the meteorological drought in Bundelkhand region located in central India. RDI has been used by many researchersfor identifying the drought characteristics as it is more suited to arid and semi-arid areas. The RDI uses precipitation as well as potential evapotranspiration (PET) and can also be used to analyse the climate change impacts on the drought scenario of a region.ThePenman-Monteith method has been used to estimate the PET. The spatio-temporal variation of drought in Bundelkhand has been investigated and it is found that every drought events has its own characteristics in terms of its areal extent, its progression, withdrawal and severity.